EXPLORING THE DECLINE OF VOLUNTARY CONSUMER ORGANIZATIONS IN TAMIL NADU - Prasad D S; M. Subala (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Voluntary consumer organizations (VCOs) play a vital role in safeguarding consumer rights, spreading awareness, and ensuring fair market practices. In Tamil Nadu, these organizations once thrived as key agents of consumer protection, advocacy, and education. However, recent trends indicate a significant decline in their active functioning and public engagement. This study aims to investigate the underlying reasons behind this downturn. Using a mixed-methods approach comprising interviews with organization members, surveys among the public, and analysis of secondary data, the research identifies critical factors contributing to the decline. Key findings suggest that inadequate financial support, limited government cooperation, lack of trained personnel, diminishing volunteer interest, and weak public outreach are among the primary causes. The study also highlights systemic challenges such as bureaucratic hurdles, political interference, and poor accountability mechanisms. Based on these insights, the paper recommends policy reforms, capacity-building initiatives, and improved coordination between stakeholders to revive and strengthen the role of VCOs in Tamil Nadu. This research contributes to the discourse on consumer rights advocacy and offers a framework for revitalizing grassroots participation in consumer movements.The main aim of the study is to identify the reasons behind the decline in active functioning of voluntary consumer organizations in Tamil Nadu. Both primary and secondary data are extensively used in this study. Then, the primary data was collected through the questionnaire method from the VOC. For collecting necessary data, 76 organisations have been collected in Tamil Nadu by using Simple random sampling technique.